Pengaruh Literasi Keuangan, Sikap Keuangan, dan Locus of Control terhadap Perilaku Keuangan di SMK Wilayah Jakarta Pusat - Kuniawan, Oktavia; Ati Sumiati; Dwi Kismayanti Respati (INDO PUBLISHING, 2025)
This study aims to determine the influence of Financial Literacy, Financial Attitude, and Locus of Control on Financial Behavior among vocational high school (SMK) students in the Central Jakarta area. The research employed a survey method using a structured questionnaire. The population consisted of students from public vocational schools in Central Jakarta, with a sample of 138 students selected through proportional random sampling. The data were analyzed using descriptive analysis, normality test, linearity test, multiple linear regression, F-test, t-test, and coefficient of determination analysis. Based on the results of the F-test, it was found that Financial Literacy, Financial Attitude, and Locus of Control simultaneously have a significant influence on Financial Behavior. Furthermore, the t-test results show that, partially: (1) Financial Literacy has a positive and significant influence on Financial Behavior; (2) Financial Attitude has a positive and significant influence on Financial Behavior; and (3) Locus of Control also has a positive and significant influence on Financial Behavior.